The importance of considering the learner psychological and cognitive aspects’ in linguistic exercises design - lanani, Okba (Journal of Human Sciences, 2021)
The learner has become the focus point of all language teaching/learning methodologies, and he is considered as a measure of success of the didactic operation or its defeat. Therefore textbooks and curricula are being designed today for the psychological, cognitive characteristics of the learner, which make each learner different from the other. All methodologies, whether they have linguistic or methodological options, propose as a main learning thechnic a set of exercises intended to lead the learner to his learning objective. Indeed, exercises analysis is important because it reveals the true goals of textbook much better than theoretical and programmatic proclamations.